THE IMPACT OF POSTURAL TRAINING ON PHYSICAL AND MENTAL READINESS IN MILITARY RECRUITS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Postural health plays a crucial role in military training, influencing both physical performance and mental resilience. This study examines the impact of structured postural training on the physical and psychological readiness of military recruits. The research was conducted among young recruits in Uzbekistan, analyzing the effects of postural exercises, ergonomic adjustments, and psychological interventions on military fitness. Results demonstrate that postural training significantly enhances endurance, flexibility, and self-confidence, reducing musculoskeletal strain and improving overall military preparedness. These findings suggest that integrating postural education into military training programs can optimize physical performance and mental resilience.